Evaluation of growth performance of three strains of Nile tilapia Orechromis niloticus (L., 1758) and relation with water physico-chemical parameters reared in brackishwater ponds, Bangladesh - Md. Mizanur Rahman Washim; A.K.M. Shafiqul Alam Rubel; Debashish Kumar Mondal; Shawon Ahmmed; Md. Hashmi Sakib; Syed Lutfar Rahman; Md. Latiful Islam (Department of Aquaculture, 2022)
This study was executed to resolve the argument on the growth superiority of three Nile tilapia strain such as, existing strain of Nile tilapia (ESNT), genetically improved farmed tilapia (GIFT) and sex reversed Monosex cultured in brackishwater pond and to comprehend the relationship of water physico-chemical parameters with the growth. Analogous age group of fish each weighing about 0.62±0.09 g with iso-stocking density (5ind./m2) and a culture tenure of 120 days was considered. The physico-chemical variables were at their optimal level over the entire time span of culture. However, all physico-chemical variable beyond alkalinity and ammonia showed strong positive correlation with mean fish weight. The study revealed that, weight gain by GIFT strain was nearly 25.9% and 5.10% higher than Monosex and ESNT strain, respectively. The highest final mean body weight was achieved in the GIFT strain (223±8.60 g) and there was significant difference among the strains. The highest apparent SGR of 16.85%/day was attained in the GIFT strain without significant variation across the strain. GIFT strain gave significantly (p<0.05) higher gross fish yield (9789.70 Kg ha-1) along with best feed conversion ratio (FCR) and survival, whereas they differed significantly among the three strains. The GIFT strain showed closest isomeric growth while the rest two had allotropic growth pattern. Thereby the results established that, strain difference significantly (p<0.05) impacted the growth parameters and GIFT was the best strain. Overall results greatly minimizes the controversy on growth pattern of different strains of Nile tilapia reared in brackishwater ponds, Bangladesh.